Enhanced Threat Detection in Experienced Riot Police Officers: Cognitive Evidence from the Face-in-the-Crowd Effect. Issue 5 (May 2014) - Damjanovic, Ljubica; Pinkham, Amy E.; Clarke, Philip; Phillips, Jeremy
We explored how varying levels of professional expertise in hostile crowd management could enhance threat detection capabilities as assessed by the face in the crowd paradigm. Trainee police officers and more experienced police officers specialized in, and having extensive experience with, riot control, were compared with participants with no experience in hostile crowd management on their search times and accuracy levels in detecting angry and happy face targets against a display of emotional and neutral distractor faces. The experienced officers relative to their trainee counterparts and nonpolice controls showed enhanced detection for threatening faces in both types of display along with a greater degree of inhibitory control over angry face distractors. These findings help to reinforce the ecological validity of the face in the crowd paradigm and provide a new theoretical link for the role of individual differences on the attentional processing of socially relevant stimuli.